Participatory Appraisal and Arrangement for Multicultural Archival Collections - Shilton, Katie; Srinivasan, Ramesh (Archivaria, 2007)
Archival theory has a long history of utilizing principles designed to preserve contextual value in records. We believe that traditional practices of appraisal, arrangement, and description can be rearticulated as participatory, community-oriented processes. This can enable context to be represented meaningfully in archives of traditionally marginalized communities. We believe this process can help build culturally relevant records repositories while enabling marginalized communities to share their experiences with a wider public. By broadening their traditional tools to actively engage marginalized communities in the preservation process, archivists can preserve local knowledge and create representative, empowered archives. RÉSUMÉ La théorie archivistique s’est longtemps servie de principes conçus pour préserver la valeur contextuelle des documents. Les auteurs pensent que les pratiques traditionnelles de l’évaluation, du classement et de la description peuvent être reformulées comme des processus participatifs et axés sur la communauté. Ceci peut permettre au contexte d’être articulé de façon significative dans les archives de communautés traditionnellement marginalisées. Ils croient que ce processus peut mener vers la création de centres d’archives plus pertinents au point de vue culturel (« culturally relevant ») tout en permettant aux communautés minoritaires de partager leurs expériences avec un plus grand public. En s’ouvrant à un plus grand éventail d’outils pour inviter les communautés marginalisées à participer au processus de préservation, les archivistes peuvent sauvegarder les connaissances locales tout en créant des archives qui font appel aux notions de la représentativité et de l’autonomisation.